Redox Regulation and Oxidative Stress in Mammalian Oocytes and Embryos Developed In Vivo and In Vitro - Madeleine L. M. Hardy (MDPI AG, 2021)
Oocytes and preimplantation embryos require careful regulation of the redox environment for optimal development both in vivo and in vitro. Reactive oxygen species (ROS) are generated throughout development as a result of cellular metabolism and enzyme reactions. ROS production can result in (i) oxidative eustress, where ROS are helpful signalling molecules with beneficial physiological functions and where the redox state of the cell is maintained within homeostatic range by a closely coupled system of antioxidants and antioxidant enzymes, or (ii) oxidative distress, where excess ROS are deleterious and impair normal cellular function. in vitro culture of embryos exacerbates ROS production due to a range of issues including culture-medium composition and laboratory culture conditions. This increase in ROS can be detrimental not only to assisted reproductive success rates but can also result in epigenetic and genetic changes in the embryo, resulting in transgenerational effects. This review examines the effects of oxidative stress in the oocyte and preimplantation embryo in both the in vivo and in vitro environment, identifies mechanisms responsible for oxidative stress in the oocyte/embryo in culture and approaches to reduce these problems, and briefly examines the potential impacts on future generations.